Delineating the Biofilm Inhibition Mechanisms of Phenolic and Aldehydic Terpenes against Cryptococcus neoformans - Kumari, Poonam (ACS Omega, 2019)
[Image: see text] The recalcitrant biofilm formed by fungus Cryptococcus neoformans is a life-threatening pathogenic condition responsible for further intensifying cryptococcosis. Considering the enhanced biofilm resistance and toxicity of synthetic antifungal drugs, the search for efficient, nontoxic, and cost-effective natural therapeutics has received a major boost. Phenolic (thymol and carvacrol) and aldehydic (citral) terpenes are natural and safe alternatives capable of efficient microbial biofilm inhibition. However, the biofilm inhibition mechanism of these terpenes still remains unclear. In this study, we adopted an integrative biophysical and biochemical approach to elucidate the hierarchy of their action against C. neoformans biofilm cells. The microscopic analysis revealed disruption of the biofilm cell surface with elevation in surface roughness and reduction in cell height. Although all terpenes acted through ergosterol biosynthesis inhibition, the phenolic terpenes also selectively interacted via ergosterol binding. Further, the alterations in the fatty acid profile in response to terpenes attenuated the cell membrane fluidity with enhanced permeability, resulting in pore formation and efflux of the K(+)/intracellular content. Additionally, mitochondrial depolarization caused higher levels of reactive oxygen species, which led to increased lipid peroxidation and activation of the antioxidant defense system. Indeed, the oxidative stress caused a significant decline in the amount of extracellular polymeric matrix and capsule sugars (mannose, xylose, and glucuronic acid), leading to a reduced capsule size and an overall negative charge on the cell surface. This comprehensive data revealed the mechanistic insights into the mode of action of terpenes on biofilm inhibition, which could be exploited for formulating novel anti-biofilm agents.